2001
DOI: 10.1128/cdli.8.2.258-265.2001
|View full text |Cite|
|
Sign up to set email alerts
|

Adherence ofGiardia lambliaTrophozoites to Int-407 Human Intestinal Cells

Abstract: Attachment of Giardia lamblia trophozoites to enterocytes is essential for colonization of the small intestine and is considered a prerequisite for parasite-induced enterocyte dysfunction and clinical disease. In this work, coincubation of Giardia with Int-407 cells, was used as an in vitro model to study the role of cytoskeleton and surface lectins involved in the attachment of the parasite. This interaction was also studied by scanning and transmission electron microscopy. Adherence was dependent on temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…5C), no cyst with anti-FLAG staining was found, in accordance with the observed difficulty of this transgenic line to form cysts. In the trophozoite stage, anti-FLAG markedly stained the cell ventral surface, nearly corresponding to specialized contractile structures with a role in G. duodenalis attachment and termed marginal groove and ventrolateral flanges (31)(32)(33). A diffuse anti-FLAG staining was also present in the nuclei and in the median body (Fig.…”
Section: Intracellular Localization Of Flag-gttll3 and Flaggdips And mentioning
confidence: 88%
“…5C), no cyst with anti-FLAG staining was found, in accordance with the observed difficulty of this transgenic line to form cysts. In the trophozoite stage, anti-FLAG markedly stained the cell ventral surface, nearly corresponding to specialized contractile structures with a role in G. duodenalis attachment and termed marginal groove and ventrolateral flanges (31)(32)(33). A diffuse anti-FLAG staining was also present in the nuclei and in the median body (Fig.…”
Section: Intracellular Localization Of Flag-gttll3 and Flaggdips And mentioning
confidence: 88%
“…It has been proposed as one important mechanism in the pathogenesis of infection. Giardiasis can cause vitamin B12 deficiency, bowel inflammation and interfere with folate absorption [9,24]. Few studies showed B12 deficiency due to giardiasis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Mandatory folate fortification of cereal flours may have created a folate-rich environment which provided optimal conditions for the adherence of Giardia trophozoites to the intestinal epithelium (53,54) . Alternatively, high levels of circulating unmetabolized folic acid from folate fortification of flour (55) have been associated with decreased innate immune function (56) .…”
Section: Discussionmentioning
confidence: 99%